Optimization of Placuna Placenta Collagen Serum on Adolescent Skin - Ariyanti Ariyanti; Eni Masruriati; Nurhidayah Nurhidayah; Anita Widiyana (Indonesian Journal of Global Health Research, 2021)
Placuna placenta has a unique character among other types of shells due to its thin and wide shell shape. The protein contained in Placuna placenta is 71% which can be used as skin nutrition. Its application to the skin can be done through collagen serum preparations. The aim of this study was to optimize the Placuna Placenta serum collagen in adolescent skin. The current research was done through an experimental study of a post-test control design in the form of a post-only controlled group design with five treatment groups with each group consisting of five skins of adolescent arms. The negative control group was given a serum base that was applied to the skin of the adolescent arm. The positive control group was given serum product x®. The test group was given Placuna Placenta shell collagen serum with the concentrations of 10%, 15% and 20%. The results showed that collagen serum can irritate the skin. In addition, the optimization of the serum collagen concentration of Placuna Placenta in adolescent skin is at a concentration of 15%. It can be summed up that optimizing the use of collagen serum on adolescent skin is a challenge in the formulation because it is beneficial for adolescent skin nutrition.